Motivasi dan Dukungan Keluarga Berpengaruh terhadap Kepatuhan Diet Penderita Diabetes Melitus Tipe 2 - Ace Sudrajat; Nesty N S; Suratun Suratun; Pramita Iriana; Wartonah Wartonah; Dewi Lusiani; Paula Krisanty; Santa Manurung (Poltekkes Kemenkes Jakarta III, 2023)
Diabetes is a chronic disease that occurs when the pancreas doesn’t produce enough insulin or when the body can’t longer use insulin effectively. Dietary compliance in patients with diabetes mellitus has very important functions including maintaining body weight, lowering blood pressure and blood sugar. Adherence to a person's DM diet is largely determined by individual motivation and family support. Lack of family support means DM sufferers usually cannot control their diet, which results in high blood sugar. The purpose of this study was to analyze the relationship between motivation and family support on dietary compliance in patients with type 2 diabetes mellitus at Pasar Rebo Health Center. This study used a descriptive analysis research design with a cross sectional approach. This research was conducted in March-May 2023. The sample in this study is 85 people and the data analysis used the chi square test. The results of the analysis showed that the test of the relationship between motivation and dietary compliance obtained a value of p = 0.261 (p>0.05) while the test of the relationship of family support and dietary compliance obtained a value of p = 0.044 (p <0.05). Based on the results, it can be concluded that there is no significant relationship between motivation and dietary compliance but there is a significant relationship between family support and dietary compliance in patients with type 2 diabetes mellitus at Pasar Rebo Health Center.